PERLINDUNGAN HUKUM BAGI PENERIMA WARALABA AKIBAT WANPRESTASI YANG DILAKUKAN PEMBERI WARALABA DALAM PERJANJIAN WARALABA - Afifah Chairunnisa; M. Sudirman; Mulyadi (Jurnal Riset Multidisiplin Edukasi, 2026)
Franchise agreements carry a high risk of default, particularly by the franchisor, who may ignore the agreement and cause losses to the franchisee. This study analyzes the legal consequences and legal protection for franchisees due to franchisor default. This study uses a juridical-normative method with a statutory, case, analytical, and conceptual approach. Data sources consist of primary, secondary, and tertiary legal materials. Qualitative data analysis was conducted through grammatical, systematic, and legal construction interpretations. The research findings demonstrate two main points. First, the legal consequences of franchisor default are multidimensional, encompassing civil, administrative, and economic impacts on the franchisee. Second, legal protection for franchisees can be sought through litigation and non-litigation mechanisms. The implications of these findings confirm that losses due to franchisor default are complex. However, franchisees have legal avenues for redress, which need to be optimized through more effective agreement enforcement and a regulatory framework.